Utilization of overground exoskeleton gait training during inpatient rehabilitation: a descriptive analysis - Jaime Gillespie; Dannae Arnold; Molly Trammell; Monica Bennett; Christa Ochoa; Simon Driver; Librada Callender; Seema Sikka; Rosemary Dubiel; Chad Swank (Journal of NeuroEngineering and Rehabilitation, 2023)
Abstract Background Overground exoskeleton gait training (OEGT) after neurological injury is safe, feasible, and may yield positive outcomes. However, no recommendations exist for initiation, progression, or termination of OEGT. This retrospective study highlights the clinical use and decision-making of OEGT within the physical therapy plan of care for patients after neurological injury during inpatient rehabilitation. Methods The records of patients admitted to inpatient rehabilitation after stroke, spinal cord injury, or traumatic brain injury who participated in at least one OEGT session were retrospectively reviewed. Session details were analyzed to illustrate progress and included: “up” time, “walk” time, step count, device assistance required for limb swing, and therapist-determined settings. Surveys were completed by therapists responsible for OEGT sessions to illuminate clinical decision-making. Results On average, patients demonstrated progressive tolerance for OEGT over successive sessions as shown by increasing time upright and walking, step count, and decreased assistance required by the exoskeleton. Therapists place preference on using OEGT with patients with more functional dependency and assess feedback from the patient and device to determine when to change settings. OEGT is terminated when other gait methods yield higher step repetitions or intensities, or to prepare for discharge. Conclusion Our descriptive retrospective data suggests that patients after neurological injury may benefit from OEGT during inpatient rehabilitation. As no guidelines exist, therapists’ clinical decisions are currently based on a combination of knowledge of motor recovery and experience. Future efforts should aim to develop evidence-based recommendations to facilitate functional recovery after neurological injury by leveraging OEGT.